Exploring ethical leadership in four Zimbabwean schools amid socio-political and economic turbulence :a multiple case study - Chingwanangwana, Bernard (My University, 2019)
There is a need and cry for ethical leadership in the schools today more than ever before, as school heads and teachers are being more and more called to accountability and integrity world over. Unethical conduct in the schools’ manifests in many ways, such as improper association, drunkenness at work, absenteeism from work, corporal punishment, embezzlement of funds and so on. There are however challenges and dilemmas associated with the discharge of ethical leadership in the schools, one such challenge is the socio-political and economic turbulence in a country. These turbulences trigger ethical leadership dilemmas and push factors upon the school heads and teachers, making ethical leadership practices difficult to practice in the schools. Basing on the current environment in Zimbabwe, this study explores the current socio-political and economic turbulences to establish its effects on ethical leadership in four schools in Marondera District. The study sought to explore the causes of ethical leadership lapses among school heads, head of departments and teachers and to find out whether the current socio-political and economic turbulence in Zimbabwe has an effect on ethical leadership in the four schools under the study. The research questions that guided this study were; What are the ethical leadership issues affecting school heads, heads of departments and teachers in four researched schools in Marondera District in Zimbabwe? Do the participants’ experience the current socio-political and economic turbulence in Zimbabwe having an effect on ethical leadership in the four schools under our study in Marondera district? Lastly, what do the participants say should be done to deal with the perceived ethical leadership challenges, if any, in the four schools in Marondera district in Zimbabwe? Using the Turbulence Theory, Virtue and Ubuntu leadership theories and employing the qualitative methodology approach, this case study explored ethical leadership in four Zimbabwean schools amid socio-political and economic turbulence. The Turbulence Theory was used to mainly elaborate on the contextual environment prevailing within the four schools in the study, while the Virtue and Ubuntu leadership theories dealt with the principle and practices expected in an ethical setting. The study was a qualitative, interpretivist multiple-case study, focusing on ethical leadership in the context of socio-political and economic turbulence in four schools in Marondera District of Zimbabwe. The data were generated through semi-structured interviews, focus There is a need and cry for ethical leadership in the schools today more than ever before, as school heads and teachers are being more and more called to accountability and integrity world over. Unethical conduct in the schools’ manifests in many ways, such as improper association, drunkenness at work, absenteeism from work, corporal punishment, embezzlement of funds and so on. There are however challenges and dilemmas associated with the discharge of ethical leadership in the schools, one such challenge is the socio-political and economic turbulence in a country. These turbulences trigger ethical leadership dilemmas and push factors upon the school heads and teachers, making ethical leadership practices difficult to practice in the schools. Basing on the current environment in Zimbabwe, this study explores the current socio-political and economic turbulences to establish its effects on ethical leadership in four schools in Marondera District. The study sought to explore the causes of ethical leadership lapses among school heads, head of departments and teachers and to find out whether the current socio-political and economic turbulence in Zimbabwe has an effect on ethical leadership in the four schools under the study. The research questions that guided this study were; What are the ethical leadership issues affecting school heads, heads of departments and teachers in four researched schools in Marondera District in Zimbabwe? Do the participants’ experience the current socio-political and economic turbulence in Zimbabwe having an effect on ethical leadership in the four schools under our study in Marondera district? Lastly, what do the participants say should be done to deal with the perceived ethical leadership challenges, if any, in the four schools in Marondera district in Zimbabwe? Using the Turbulence Theory, Virtue and Ubuntu leadership theories and employing the qualitative methodology approach, this case study explored ethical leadership in four Zimbabwean schools amid socio-political and economic turbulence. The Turbulence Theory was used to mainly elaborate on the contextual environment prevailing within the four schools in the study, while the Virtue and Ubuntu leadership theories dealt with the principle and practices expected in an ethical setting. The study was a qualitative, interpretivist multiple-case study, focusing on ethical leadership in the context of socio-political and economic turbulence in four schools in Marondera District of Zimbabwe. The data were generated through semi-structured interviews, focus There is a need and cry for ethical leadership in the schools today more than ever before, as school heads and teachers are being more and more called to accountability and integrity world over. Unethical conduct in the schools’ manifests in many ways, such as improper association, drunkenness at work, absenteeism from work, corporal punishment, embezzlement of funds and so on. There are however challenges and dilemmas associated with the discharge of ethical leadership in the schools, one such challenge is the socio-political and economic turbulence in a country. These turbulences trigger ethical leadership dilemmas and push factors upon the school heads and teachers, making ethical leadership practices difficult to practice in the schools. Basing on the current environment in Zimbabwe, this study explores the current socio-political and economic turbulences to establish its effects on ethical leadership in four schools in Marondera District. The study sought to explore the causes of ethical leadership lapses among school heads, head of departments and teachers and to find out whether the current socio-political and economic turbulence in Zimbabwe has an effect on ethical leadership in the four schools under the study. The research questions that guided this study were; What are the ethical leadership issues affecting school heads, heads of departments and teachers in four researched schools in Marondera District in Zimbabwe? Do the participants’ experience the current socio-political and economic turbulence in Zimbabwe having an effect on ethical leadership in the four schools under our study in Marondera district? Lastly, what do the participants say should be done to deal with the perceived ethical leadership challenges, if any, in the four schools in Marondera district in Zimbabwe? Using the Turbulence Theory, Virtue and Ubuntu leadership theories and employing the qualitative methodology approach, this case study explored ethical leadership in four Zimbabwean schools amid socio-political and economic turbulence. The Turbulence Theory was used to mainly elaborate on the contextual environment prevailing within the four schools in the study, while the Virtue and Ubuntu leadership theories dealt with the principle and practices expected in an ethical setting. The study was a qualitative, interpretivist multiple-case study, focusing on ethical leadership in the context of socio-political and economic turbulence in four schools in Marondera District of Zimbabwe. The data were generated through semi-structured interviews, focus group interviews, questionnaires and documents analysis. The study adhered to all ethical issues in research before and during data generation. To ensure trustworthiness of the findings, the study employed multiple data generation instruments, such as; semi structured interviews, focus group interviews, questionnaires and documents review. Content analysis was applied to analyse the data. The conclusions arrived at indicate that the current socio-political and economic turbulence prevailing in Zimbabwe has adverse effect on the exercise of ethical leadership in schools in Marondera District. The major effects being on the poor teacher remuneration, lack of resources in the schools, political violence on teachers, rampant absenteeism by both teachers and learners and improper associations. Based on the findings, the study recommends an all stake holder approach to address the issues of socio-political and economic turbulences to enable school personnel to have an environment conducive of discharging ethical leadership in the schools. It further recommends the restoration of funding structures in these schools and competitive remuneration for school personnel. A Turbulence Intervention Model was developed, which could help deal with these ethical leadership challenges in the schools:
A thesis submitted in the fulfilment of the academic requiments for the Degree of Doctor of Philosophy to the Faculty of Humanities, School of Education at the University of Witwatersrand, Johannesburg 2019
Keywords: Leadership--Moral and ethical aspects; Educational leadership